The 1st International Electronic Conference on Biomolecules: Natural and Bio-Inspired Therapeutics for Human Diseases 2020
DOI: 10.3390/iecbm2020-08806
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Urolithin A—A Natural Polyphenol Metabolite of Ellagitannins as a Modulator of the Gut Microbiota for Its Potential Use in Obesity Therapy

Abstract: Obesity, a global health concern is associated with the dysbiosis of intestinal microbial composition. This study aims to investigate the potentials of urolithin A (Uro-A), in reducing body weight gain through the modulation of the gut microbiota. Rats were fed on a high-fat diet and administered with Uro-A. Changes in the composition of the gut microbial community were analyzed using 16S rDNA gene sequencing. Our results showed that Uro-A significantly decreased body weight gain and modulated the compositions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Wistar rats were divided randomly into four groups (n = 6): a control group, a DOX group, a URO A at 2.5 mgkg −1 with DOX group, and a URO A at 5 mgkg −1 with DOX group ( Figure 1 ). URO A doses were based on an earlier study [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Wistar rats were divided randomly into four groups (n = 6): a control group, a DOX group, a URO A at 2.5 mgkg −1 with DOX group, and a URO A at 5 mgkg −1 with DOX group ( Figure 1 ). URO A doses were based on an earlier study [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of Soluble Aβ Levels. We used sandwich ELISA method to detect the soluble Aβ levels, as previously described in Manczak et al 2016 [ 25 ] and Manczak et al 2018 [ 48 , 49 , 50 ]. For this method, 96-well plate was used, and the procedure was performed by following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…EA metabolism and urolithin production vary according to host health, age, gut microbial composition, environmental conditions, and metabotypes [14,119,131,132]. The presence of specific bacterial genera such as Gordonibacter and Ellagibacter has been shown to be necessary for the conversion of EA into urolithins [118,119,133,134]. Two gut microbial species, Gordonibacte urolithinfaciens and Gordonibacte pamelaeae, can produce urolithin C, whereas Ellagibacter isourolithinfaciens produces isourolithin A [132,135,136].…”
Section: Ellagic Acid Metabolitesmentioning
confidence: 99%
“…New insights into research on EAs have focused on its microbial metabolites, the urolithins. According to Abdulrahman and colleagues [133], supplementation of urolithin A to HFD-fed Wistar rats, reduced bodyweight, serum levels of cholesterol and low-density lipoprotein (LDL), and increased levels of high-density lipoprotein (HDL). Moreover, this study demonstrated that urolithin A administration reduced the abundance of the specific microbiome related to weight gain, dysfunction of lipid metabolism, and impaired glucose metabolism, suggesting urolithin A has the potential to act as a therapeutic agent in obesity [133].…”
Section: Therapeutic Efficacymentioning
confidence: 99%
See 1 more Smart Citation